Efek aktivator EM4 dan RJ37 formula turbo neo aktiv terhadap laju pengomposan dan kualitas kompos ampas sagu - Boari, Marsalina; Musaad, Ishak; Noya, Alce Ilona; Abbas, Barahima (Program Pascasarjana Universitas Papua, 2024)
ABSTRACT: This research aims to determine the composting rate and quality of sago dregs compost using EM4 and RJ37 Formula Turbo Neo Aktiv (FTNA) activators. The sago dregs composting process with EM4 and RJ37 FTNA activator treatment has an effect on the composting rate and quality of the sago dregs compost. The research used a single factor Randomized Block Design. Parameters observed include C-Organic content, N, P, K, C/N ratio, plant height, number of leaves and wet weight at harvest. The research results showed that EM4 and RJ37 FTNA with doses of 100 ml and 150 ml could accelerate the composting rate of sago dregs for 8 weeks so as to obtain compost quality according to the SNI 19-7030-2004 criteria